Quantifying Antimicrobial Exposure in Dogs From a Longitudinal Study - Méndez, María; Moreno, Miguel A. (Frontiers in Veterinary Science, 2020)
Bacterial resistance to antimicrobials (AMR) is a growing public health threat and exposure to antimicrobials (AMs) is, on the whole, the major risk factor for the occurrence of AMR. During the past decade a limited number of studies about AM exposure in dogs have been published, showing a noticeable diversity regarding numerators (AMU), denominators (population at risk) and indicators. The aim of this study is to show that metrics based on the most easily recorded data about treatments and a follow-up design are a promising method for a preliminary assessment of AM exposure in companion animals when more detailed data are not available. To quantify AM exposure, two simple indicators were used: number of treatments (Ts) per 100 dogs, and number of treatments per 10 dog-years. Overall figures of AM exposure were 194 Ts/100_dogs (480 treatments and 248 dogs) and 18.4 Ts/10_dog-years (480 treatments and 95,171 dog-days), respectively. According to the administration route, AM exposure figures were 126 Ts/100 dogs (305 treatments and 242 dogs) and 12.1 Ts/10_dog-years (305 treatments and 92,059 dog-days) for systemic use and 66 Ts/100 dogs (160 treatments and 242 dogs) and 6.3 Ts/10_dog-years (160 treatments in 92,059 dog-days) for topical use. Since there is no current agreement regarding an indicator for quantifying AM exposure in dogs, in addition to other measures, the simplest indicators based on the most frequently available information should also be reported as a preliminary compromise for permitting a comparative analysis of the different scenarios.